2012
DOI: 10.1037/a0024816
|View full text |Cite
|
Sign up to set email alerts
|

Musicians experience less age-related decline in central auditory processing.

Abstract: Age-related decline in auditory perception reflects changes in the peripheral and central auditory systems. These age-related changes include a reduced ability to detect minute spectral and temporal details in an auditory signal, which contributes to a decreased ability to understand speech in noisy environments. Given that musical training in young adults has been shown to improve these auditory abilities, we investigated the possibility that musicians experience less age-related decline in auditory perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
186
9
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(226 citation statements)
references
References 54 publications
22
186
9
9
Order By: Relevance
“…Given that both music training and JROTC training enhance phonological awareness and involve synchronization with perceptual cues, future work comparing music training to a passive control group could reveal a divergence not reported here. On the other hand, we found no gains in rapid naming or phonological memory, despite the fact that both reading (46)(47)(48)(49)(50) and verbal memory (30)(31)(32)(33)(34)(35)(36)(37)(38) have been associated with music training in other studies, suggesting either that the training studied here was not optimally designed to enhance these skills or that enhancing these skills requires a greater amount of training or training begun earlier in life. A third possibility is that the link between phonological processes and beat synchronization is restricted to phonological awareness.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Given that both music training and JROTC training enhance phonological awareness and involve synchronization with perceptual cues, future work comparing music training to a passive control group could reveal a divergence not reported here. On the other hand, we found no gains in rapid naming or phonological memory, despite the fact that both reading (46)(47)(48)(49)(50) and verbal memory (30)(31)(32)(33)(34)(35)(36)(37)(38) have been associated with music training in other studies, suggesting either that the training studied here was not optimally designed to enhance these skills or that enhancing these skills requires a greater amount of training or training begun earlier in life. A third possibility is that the link between phonological processes and beat synchronization is restricted to phonological awareness.…”
Section: Discussioncontrasting
confidence: 49%
“…Studies comparing nonmusicians with musicians who began training early in life have revealed a "signature" set of enhancements associated with musical experience (27,28). Relative to nonmusician peers, musicians tend to show enhanced speech-innoise perception (29)(30)(31)(32)(33)(34), verbal memory (30)(31)(32)(33)(35)(36)(37)(38), phonological skills (39)(40)(41)(42)(43)(44)(45), and reading (46-50), although not without exception (51,52). Music training has also been linked to enhancements in the encoding of sound throughout the auditory system.…”
mentioning
confidence: 99%
“…Zendel & Alain, 2012), and on average had 12.6 years of experience (SD = 7.19). The musicians reported playing between one and four different instruments (M = 2.16, SD = 1.19), with 60 % playing more than one instrument.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Studies documenting training-related differences are important because they suggest that formal musical training might have beneficial effects across the lifespan, such as boosting sensory and cognitive function (Schellenberg, 2004;Zendel & Alain, 2012). One limitation to enacting the potential benefits of music in the broader population is that not everyone has the time, money, or perseverance to learn an instrument.…”
mentioning
confidence: 99%
“…For those who continue into college or beyond, the sensory, cognitive, and neural benefits of long-term musical training are clear (Schneider et al, 2002;Musacchia et al, 2007;Patel and Iversen, 2007;Parbery-Clark et al, 2009Zendel and Alain, 2012). Yet, we have an incomplete understanding of how such training influences the adult brain when music lessons begin and end before adulthood.…”
Section: Introductionmentioning
confidence: 99%